2010
DOI: 10.1111/j.1365-3156.2010.02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D supplementation to children diagnosed with pneumonia in Kabul: a randomised controlled trial

Abstract: Summaryobjectives To determine whether (i) supplementation of oral 100 000 iu of vitamin D 3 (cholecalciferol) along with antibiotics will reduce the duration of illness in children with pneumonia; (ii) supplementation will reduce the risk of repeat episodes.methods Double-blind individually randomised placebo-controlled trial in an inner-city hospital in Kabul, of 453 children aged 1-36 months, diagnosed with non-severe or severe pneumonia at the outpatient clinic. Children with rickets, other concurrent seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 27 publications
(33 reference statements)
0
95
1
3
Order By: Relevance
“…The role of vitamin D supplementation in the treatment of pneumonia in children was explored in a placebo controlled trial in Kabul, Afghanistan 21. A total of 453 children aged 1 month–3 years who were diagnosed with pneumonia at an outpatient clinic were randomised to receive a single oral dose of 100 000 units of vitamin D 3 or placebo.…”
Section: Introductionmentioning
confidence: 99%
“…The role of vitamin D supplementation in the treatment of pneumonia in children was explored in a placebo controlled trial in Kabul, Afghanistan 21. A total of 453 children aged 1 month–3 years who were diagnosed with pneumonia at an outpatient clinic were randomised to receive a single oral dose of 100 000 units of vitamin D 3 or placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are limited studies looking at the effect of vitamin D intervention in children, most publications show a beneficial effect of vitamin D supplementation on reducing acute respiratory tract infections [151,152]. A randomized controlled trial looking at the effect of 100,000 IU of vitamin D supplementation in South Asian children with pneumonia showed a reduced number of repeat attacks in the vitamin D group (58%; RR 0.78; 95% CI 0.64-0.94; p = 0.01) [153]. However, supplementation with the same dose once every 3 months for a period of 18 months did not reduce the prevalence of pneumonia in high-risk South Asian infants [154].…”
Section: Link Between Vitamin D and Immune Function - Evidence From Imentioning
confidence: 99%
“…A randomised control trial in an area of high vitamin D deficiency in Afghanistan showed that one high dose of vitamin D 3 combined with antibiotic treatment reduced the reoccurrence of pneumonia in children aged 1 -36 months who had been hospitalised for pneumonia. [41] However, there are conflicting results from another randomised, placebo-controlled trial by the same group in the same area. Oral vitamin D 3 (100 000 IU, n=1 524) was compared with a placebo (n=1 522) and given to children aged 1 -11 months in Kabul, Afghanistan.…”
Section: Vitamin D Pneumonia and Urtismentioning
confidence: 96%